The Difference in Effectiveness of Soy Extract and Mung Bean Extract on Reducing Hot Flash Symptoms in Menopausal Women - Mayang Citra Hariati (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2026)
During the climacteric period, there is a decline in ovarian function and hormone production. The decrease in estrogen hormone often causes vasomotor symptoms, especially hot flashes, which can disrupt daily activities and reduce the quality of life of menopausal women. The use of foods containing phytoestrogens, such as soybeans and mung beans, has become one of the non-pharmacological therapy alternatives that is considered safer to help reduce these symptoms. This study aims to determine the difference in the effectiveness of administering soybean extract and mung bean extract on the reduction of hot flash symptoms in menopausal women. This study uses a quasi-experimental design with a pretest–posttest with non-control design. The study was conducted at Pratama Cahaya 2 Clinic in January–February 2026. The study sample consisted of 36 menopausal women selected using purposive sampling technique. The respondents were divided into two intervention groups, namely the group given soybean extract and the group given mung bean extract, each 250 ml per day for 14 days. Hot flash symptoms were assessed using the Hot Flashes Rating Scale (HFRS) instrument. Data analysis used a paired t-test to observe changes before and after the intervention, and an independent t-test to compare the effectiveness of the two groups with a confidence level of 95% (p < 0.05). The results of the study showed that both interventions were able to significantly reduce hot flash symptoms. In the soybean extract group, an average reduction of 4.683 ± 0.6784 (p = 0.000) was obtained, while in the mung bean extract group, the average reduction was 4.050 ± 0.5649 (p = 0.000). The independent t-test results showed a difference in effectiveness between the two groups with t = 3.271 and p = 0.002 (p < 0.05). The group that consumed soybean extract showed a greater decrease in hot flash symptoms compared to the group that consumed mung bean extract. Conclusion: There is a difference in effectiveness between administering soybean extract and mung bean extract in reducing hot flash symptoms in menopausal women. Soybean extract has been proven to be more effective than mung bean extract in reducing both the frequency and intensity of hot flashes.